Learning from the Political Wisdom of Indonesia’s Founding Fathers: An Analytical Study of K.H. A. Wachid Hasjim’s Political Thought on Islam–State Relations - Ahmad Asroni (Jurnal Ushuluddin, 2025)
This article examines the political wisdom and contributions of K.H. A. Wachid Hasjim in the formulation of Indonesia’s state foundation and constitution during the BPUPK and PPKI sessions. Drawing on a qualitative, historical–descriptive approach using documentary research, this study analyzes primary sources—including the BPUPK and PPKI deliberations, writings of Wachid Hasjim, and constitutional documents—as well as secondary scholarly works. The findings show that despite being a strong advocate for Islam as the basis of the state, K.H. A. Wachid Hasyim demonstrated remarkable magnanimity by accepting the removal of the Jakarta Charter and several Islamic formulations in the 1945 Constitution for the sake of national unity. This study argues that Hasjim's thought represents a 'symbiotic paradigm' rooted not merely in political compromise but in a substantive understanding of Islamic jurisprudence (fiqh) that prioritizes public good (maslahah). His approach reflects a broader principle that Pancasila, as a compromise-oriented and accommodating state ideology, provides a framework that guarantees religious freedom while maintaining national cohesion. The study highlights the relevance of his political wisdom in contemporary Indonesia, where political and religious elites often succumb to pragmatism, egoism, and intolerance, contributing to social and religious conflicts. Emulating K.H. A. Wachid Hasyim’s inclusive and tolerant leadership can serve as a model for fostering national unity and harmonious religious coexistence in Indonesia’s pluralistic society.